Effects of motor movement training on athletes' neural activity and causal relationship of these activities [KOMPLEKS MOTOR HAREKET EǦITIMININ SPORCULARDAKI NÖRONEL AKTIV ASYONLARA ETKISI VE BU AKTIV ASYONLARIN NEDENSELLIK ILIŞKISININ INCELENMESI] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
Recently, there are lots of studies that perform research on causal relationship between electrcial activations of different brain regions. Coherence studies, also provides new methods for deep understanding of those relationhips. Strength, direction and origin of activation between two or more electrodes are assessed in coherence studies. However, these studies are not sufficient in terms of both their methodology and results. In many of coherence studies, EEG recordings were performed during resting conditions with eyes open and closed, or during sleep. Results were analyzed to investigate causal relationships between electrode activations in these states. Based on those studies, same procedure was used in the current study. Oscillatory activations of football players who were recruited for complex motor movement training, and of control group were measured during eyes open and closed conditions with EEG. Furthermore EEG recordings were taken before and after training from both experimental and control group. The results were analyzed to find differences in electrode activations in pre and post tests, and to understand causal relationships between activations of different electrodes. It is found that there are differences in brain activations of experiment group between pre and post tests. © 2015 IEEE.
Keywords: Causal relationship; Coherence; Complex Motor Movement Training; Sports